PENGARUH CSR TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN LEVERAGE SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR SUB SEKTOR CONSUMER NON CYCLICALS BEI 2021-2024) - Bani Miftah Rafi; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
Financial performance is a critical indicator in evaluating the health and competitiveness of companies, particularly in the consumer non-cyclicals sector, which is essential for meeting the basic needs of the community. One significant factor influencing financial performance is the implementation of Corporate Social Responsibility (CSR). CSR not only serves as a form of social and environmental responsibility but also acts as a corporate strategy to enhance legitimacy and garner stakeholder support.This study aims to analyze the impact of CSR on financial performance, with leverage as a moderating variable, in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The research focuses on understanding how CSR activities influence financial outcomes and whether leverage can amplify or moderate this effect.The study employs a quantitative approach, using secondary data from annual reports and sustainability reports. Data analysis was conducted using multiple linear regression with SPSS version 27, utilizing a sample of 39 companies over a four-year observation period, resulting in156 observations. The findings indicate that CSR positively affects financial performance. Furthermore, leverage is found to strengthen the relationship between CSR and financial performance, suggesting that the use of debt can motivate companies to optimize CSR activities, thereby improving their financial performance